THE EFFECTIVENESS OF FABLES ON THE ETHICS OF POLITE GRADE VII STUDENTS IN INDONESIAN LANGUAGE LEARNING - Sisi Rosida (JOLADU: Journal of Language Education, 2025)
This study analyzes the effect of using fable stories on the ethics of politeness of seventh-grade students in learning Indonesian. The background of the study was driven by the issue of declining ethics of politeness of students due to exposure to negative digital content. Fables were chosen as an effective media because they contain moral messages through animal characters, making them interesting and appropriate to the stage of students' cognitive development. This study used a Quasi-Experimental Design with a One Group Pretest-Posttest model. The research sample consisted of 54 seventh-grade students. The learning outcomes of ethics of politeness were measured through pretest and posttest. The data were then analyzed using a t-test after fulfilling the normality and homogeneity tests. The results showed a significant increase in the average score, namely from 69.9 (pretest) to 82.8 (posttest). The results of the t-test showed that the calculated t-value (9.6) was greater than the t-table (1.6736). The hypothesis was accepted, which concluded that the use of fables was effective in improving students' ethics of politeness. These findings confirm that fables are a valid strategy for shaping students' character and ethics.